Game theory and fuzzy programming approaches for bi-objective optimization of reservoir watershed management: a case study in Namazgah reservoir - Ucler, N.; Engin, G. Onkal; Kocken, H. G.; Oncel, M. S. (SPRINGER HEIDELBERG, 2015)
In this study, game theory and fuzzy programming approaches were used to balance economic and environmental impacts in the Namazgah reservoir, Turkey. The main goals identified were to maximize economic benefits of land use and to protect water quality of reservoir and land resources. Total phosphorous load (kg ha(-1) year(-1)) and economic income (USD ha(-1) year(-1)) from land use were determined as environmental value and economic value, respectively. The surface area of existing land use types, which are grouped under 10 headings according to the investigations on the watershed area, and the constraint values for the watershed were calculated using aerial photos, master plans, and basin slope map. The results of fuzzy programming approach were found to be very close to the results of the game theory model. It was concluded that the amount of fertilizer used in the current situation presents a danger to the reservoir and, therefore, unnecessary fertilizer use should be prevented. Additionally, nuts, fruit, and vegetable cultivation, instead of wheat and corn cultivation, was found to be more suitable due to their high economic income and low total phosphorus (TP) load. Apart from agricultural activities, livestock farming should also be considered in the area as a second source of income. It is believed that the results obtained in this study will help decision makers to identify possible problems of the watershed.
Keywords: Reservoir watershed management; Game theory; Fuzzy programming; Bi-objective optimization; RIVER-BASIN; MULTIOBJECTIVE OPTIMIZATION; IMPACTS; MODEL; Environmental Sciences & Ecology